(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
The Moscovian Stage of Central European Russia is represented by a cyclic shallow-marine carbonate succession deposited in a gentle ramp setting part of a vast epeiric sea. Fusulinoids occur in all the marine lithofacies studied including most extreme intertidal grainstones. The ecological tolerance of fusulinoids decreases in the following order: Fusiella, Schubertella, Ozawainella, Fusulinella, Fusulina, Reitlingerina and Hemifusulina, Neostaffella, and Parastaffelloides. The scarcity of Taitzehoella, Beedeina, Eostaffella, Kamaina, and Praeobsoletes did not allow the reliable estimation of their facies distribution and tolerance. Three main zones of fusulinoid distribution are revealed. The predominantly autochthonous assemblages of these zones probably correspond to original fusulinoid biofacies. Biofacies 1 contains the most tolerant genera Fusiella and Schubertella that lived in the most severe conditions of the restricted peritidal zone. The optimal shallow normal-marine settings of Biofacies 2 maintained the highest diversity of fusulinoids (Fusiella, Schubertella, Ozawainella, Fusulinella, Fusulina, Reitlingerina, Hemifusulina, Neostaffella, Parastaffelloides, Taitzehoella, Beedeina, Eostaffella, Kamaina, and Praeobsoletes). Most abundant were Fusulinella, Fusulina, and Schubertella. The habitats of staffellids (Reitlingerina and Parastaffelloides) were shifted from a wide normal-marine facies spectrum in Podolskian time to less favourable settings of shoals and fine small-foraminiferal sands. The apparent peaks of some genera in the shoal lithofacies of coarse skeletal-peloidal grainstones must be increased several times as a consequence of much slower net sediment accumulation, but the ratio of different fusulinoid genera in this lithofacies is probably retained. Biofacies 3 contains distal tempestites and skeletal mudstones representing the deepest (considerably more than 20 m) depositional environments. The fusulinoid assemblage is less diverse than in Biofacies 2. In the Upper Gubastovo tempestites, Biofacies 3 is highly dominated by Hemifusulina bocki Moeller. Fusiella, Schubertella, Ozawainella, Taitzehoella, Fusulinella, and Fusulina occur in lesser quantities. Some of these infrequent fusulinoids may be allochthonous, and the original diversity might have been even lower. Hemifusulina in the Upper Gubastovo tempestites tends to form monospecific (H. bocki Moell.) concentrations exhibiting the signs of sudden storm burial.